Unveiling the occurrence of vulnerable Sisorid catfish (Teleostei: Sisoridae) in Bangka based on morphological and molecular evidence - FITRI S. VALEN; NOORHIDAYAH B. MAMAT; JOSIE SOUTH; FELIPE P. OTTONI; LUCAS O. VIEIRA; AHMAD S. KAMARUDIN; AHMAD Y. AFANDI; VERYL HASAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Valen FS, Mamat NB, South J, Ottoni FP, Vieira LO, Kamarudin AS, Afandi AY, Hasan V. 2024. Unveiling the occurrence of vulnerable Sisorid catfish (Teleostei: Sisoridae) in Bangka based on morphological and molecular evidence. Biodiversitas 25: 4543-4550. Glyptothorax robustus Boeseman 1966 is a vulnerable catfish species that is known to be distributed across Java and Sumatra. The objective of this research is to document, for the first time, the presence of G. robustus in Bangka, Indonesia, and to update the species' geographic distribution. This discovery of a freshwater fish in a new location significantly contributes to the understanding of its biogeography. A purpose-sampling approach was employed to collect the specimens. The species were identified morphologically and molecularly through DNA barcoding. On 20 January 2023, five G. robustus specimens were collected from the Bumang River in Bangka Island using fish traps. The occurrence of G. robustus at this location represents the most northerly record of this species and extends its known geographic range. Additionally, this new site is approximately 200 km north of the nearest known location on Sumatra Island and 300 km north of the nearest known location in Java. This record expands the documented distribution range of G. robustus and enhances our understanding of this species. Furthermore, an updated record of the G. robustus DNA sequence from the cytochrome c oxidase subunit I (COI) gene is presented. This sequence constitutes the first DNA barcode for Indonesia and has the potential to support future studies in biogeographical and ichthyological research. The DNA sequence was registered in NCBI GenBank under the accession code OR144414. This DNA barcode can serve as a standard for identifying G. robustus and will support future DNA and biotechnology-based studies.